2023
DOI: 10.2174/1871527321666220406105844
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Catatonia: New Insights from the Autism Spectrum

Abstract: Initially conceptualized as a subtype of schizophrenia, catatonia has progressively been recognized to occur in a broad variety of conditions, as a kind of final common pathway for many severe men-tal disorders. There is a significant overlap between the fundamental symptoms of Autism Spectrum Disorder (ASD) and catatonia, and ASD can frequently complicate with catatonic states. While provocative, the hypothesis that neuroatypicality may represent the submerged structural piece un-derlying catatonic states is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Numerous clinical features are shared by ASD and catatonia, such as mutism and echolalia, stereotyped movements and repetitive behaviors, and negativism and arousal. This clinical overlap could be responsible, on one hand, for a propensity to overestimate subthreshold catatonia among autistic subjects and, on the other, for a failure to recognize catatonic symptoms that first appear in patients with ASD [ 11 ]. Indeed, although anecdotal, previous descriptions have indicated that catatonia may slowly develop over the course of autism, often preceded by isolated manifestations and a slow deterioration in functioning, until it assumes a chronic character [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical features are shared by ASD and catatonia, such as mutism and echolalia, stereotyped movements and repetitive behaviors, and negativism and arousal. This clinical overlap could be responsible, on one hand, for a propensity to overestimate subthreshold catatonia among autistic subjects and, on the other, for a failure to recognize catatonic symptoms that first appear in patients with ASD [ 11 ]. Indeed, although anecdotal, previous descriptions have indicated that catatonia may slowly develop over the course of autism, often preceded by isolated manifestations and a slow deterioration in functioning, until it assumes a chronic character [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…22,31,42,57,58,62,63 In particular, the presence of AT, which results in reduced coping strategies and difficulties in processing stressful experiences, may lead to an increased vulnerability to a wide range of trauma or stress-related symptom. 22,42,44,57,58,61,63 Considering that subjects with AT may have difficulties also in emotional expression and impairment in peer relationships, the lack of ability to request and obtain social support may enhance the negative impact of the stressors. 22,29,39,42,57,58,61,63 Noticeably, the autism spectrum group reported higher scores also on TALS domain, investigating the wide spectrum of loss events and potentially traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…22,42,44,57,58,61,63 Considering that subjects with AT may have difficulties also in emotional expression and impairment in peer relationships, the lack of ability to request and obtain social support may enhance the negative impact of the stressors. 22,29,39,42,57,58,61,63 Noticeably, the autism spectrum group reported higher scores also on TALS domain, investigating the wide spectrum of loss events and potentially traumatic events. These domains do not assess only major traumatic or loss events but also minor ones for which the subject experienced distress (such as changes in home or school, school or work failures, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations